APPLICATION OF SCHEDULED ACTIVITIES READING THE QUR'AN IN PATIENTS WITH SENSORY PERCEPTION DISORDERS: HEARING HALLUCINATIONS AT CIGEUREUNG HEALTH CENTER - Asep Riyana; Fitriani, Anisa; Kustiawan, Ridwan (Jurnal Kesehatan Mahardika, 2024)
One of the symptoms that appear in people with schizophrenia is auditory hallucinations. The way to prevent hallucinations from appearing is with scheduled activities. The purpose of this case study is to describe the characteristics of the patient, describe the strategy for scheduled activities reading the Qur'an and describe the decrease in symptoms before and after therapy. This scientific writing method is. The results of the assessment of the case studies of the two clients which were carried out by measuring signs and symptoms found one diagnosis that emerged, namely auditory hallucinations. The evaluation results for 5 days showed that both patients experienced a decrease in signs and symptoms on client 1 80% and on client 2 66%. It can be concluded that the results of this study show that scheduled Qur'an reading therapy is effective in reducing hallucinations and increasing the ability to control hallucinations. Suggestions for families to be able to monitor the client's scheduled Al-Qur'an reading activities and continue to motivate them to carry out positive activities for clients with sensory perception disorders: auditory hallucinations, so that patients feel there is support that can speed up the healing process of their illness.